Students’ Perceptions of Language Anxiety in Speaking Classes - Kayaoğlu, Mustafa Naci; Sağlamel, Hasan (Journal of History Culture and Art Research, 2013)
Abstract A considerable number of foreign as well as second language learners suffer from language anxiety when they step into the language classroom. What makes language learning environments, particularly English language learning situations, anxiety provoking has been well-established in language anxiety literature and the learners’ perception of language anxiety deserve a special mention as they are one of the parties directly involved in learning process. To this end, this study aims at exploring learners’ perceptions of language anxiety in speaking classes at a north-eastern state university in Turkey. Through a purposive sampling procedure, 30 students from different proficiency levels were interviewed. Findings from the semi-structured interviews are discussed with reference to learners’ perceptions of learning English. Possible sources and manifestations of language anxiety from the learners’ perspectives are examined and their suggested ways to lower language anxiety are discussed.